Characterisation of Polymesoda bengalensis Shell Powder - Mahsuri, Yusof; Nur Tahirah, Razali; Marini, Sawawi; Kuan, Nicholas Hoo Tien; Dexter Sigan, John (UNIMAS Publisher, 2020)
Seafood shell is abundant and has no eminent use and thus, commonly regarded as waste.Reusing and converting it into a useful material can decrease the amount of waste.Therefore, a study of the crystalline structure should be performed before identifying the potential use of the material. Theaim of this study istoidentifythe element and polymorph of Polymesoda bengalensis shell. The characterisations involved the usage of X-ray powder diffraction (XRD), scanning electron microscope (SEM)andenergy-dispersive X-ray spectroscopy (EDX). The XRD study revealed that theshellpowder mostly consisted of aragonite. The analysis from SEM also revealed that the aragonite was in the form of rod-like crystal. The morphology of sectional, inner and outer surfaces of the shell was s foundthat the aragonite was arranged in the form of a cross-lamellar structure of various sizes. The elemental content of the shell showed that CaCO3in this shell contained large amounts of calcium and carbon.